반려식물 키트 산업의 활성화 방안에 관한 연구 - 산업 종사자의 수요를 중심으로 - 노회은; Roh Hoi-eun; 임채준; Lim Chae-jun; 이민지; Lee Min-ji; 조장환; Jo Jang-hwan (한국조경학회지, 2024)
본 연구의 목적은 반려식물 키트 산업의 현황을 파악하고, 산업 활성화를 위한 지원 정책 우선순위를 알아보는 것이다. SWOT 분석을 통해 반려식물 키트 산업의 현황을 진단하였고, 산업 활성화를 위한 지원 정책 우선순위 파악을 위해 반려식물 키트 산업 종사자를 대상으로 계층분석을 활용하였다. SWOT 분석 결과, SO 전략으로는 정부의 지원 정책을 활용하여 마케팅을 강화하고 친환경 이미지와 DIY 키트를 결합한 제품을 개발하는 것이며, WO 전략으로는 시장 인지도를 높이기 위한 광고 캠페인을 전개하고 유통망 확장을 위한 전략적 파트너십을 구축하는 것으로 나타났다. 또한, ST 전략으로는 경제 불확실성에 대응하여 가격 경쟁력을 강화하고 경쟁 제품 대비 차별화된 고유가치를 제안하는 것이며, WT 전략으로는 비용 절감을 위한 생산 공정을 개선하고 소비자 피드백을 반영하여 제품품질을 개선하는 것으로 나타났다. AHP 분석 결과 총 3개의 상위항목과 12개의 하위항목으로 구성한 평가 항목을 도출하였고, 전문가 설문을 통해 총 17부의 데이터를 수집하였다. 분석 결과, ‘진입 단계’ (0.482), ‘활성화 단계’(0.397), ‘고도화 단계’ (0.121) 순의 중요도가 도출되었다. 또한 ‘간담회 개최’(0.181)가 가장 중요한 하위항목으로 나타났으며, ‘키트 개발 지원’(0.020)은 상대적으로 낮은 중요도를 보였다. 반려식물 키트 산업은 정원 산업 발전을 위한 초기 단계 사업으로 적절한 정책적 인큐베이팅은 정원 산업 활성화에 도움을 줄 수 있다. 본 연구의 결과는 반려식물 키트 산업 활성화를 위한 산업계의 수요에 대한 기초 정보를 제공할 수 있다. The purpose of this study is to understand the current status of the pet plant kit industry and determine the priorities for support policies to revitalize the industry. SWOT analysis assessed the industry's current state, and the Analytic Hierarchy Process (AHP) was used with industry professionals to prioritize support policies. The SWOT analysis results indicated that SO strategies involve leveraging government support policies to enhance marketing and developing eco-friendly DIY products. WO strategies include launching advertising campaigns to increase market recognition and establishing strategic partnerships to expand distribution. ST strategies focus on strengthening price competitiveness and proposing unique values, while WT strategies involve improving production processes and enhancing product quality based on consumer feedback. The AHP analysis identified 3 top-level and 12 sub-level evaluation items, with data collected from 17 expert surveys. The results showed the 'entry phase' (0.482), 'activation phase' (0.397), and 'advanced phase' (0.121) were prioritized, with 'organizing seminars' (0.181) as the most crucial subcategory and 'support for kit development' (0.020) as the least. The pet plant kit industry is in its early stages, and appropriate policy incubation can help activate the garden industry. This study provides foundational information on the industry's needs for activation.